Roles of the Everyday: Potential Impacts of Architectural Recycling as a Key for the Transition (EAAE Annual Conference Proceedings, 2025)
Addressing the diffuse city from a perspective of ecological transition1 allows us to broaden the horizons of heritage adaptation to an interpretation of everyday architecture (2) as a resource.The contribution investigates recycling projects (3) that enhance their resources out of the building’s borders, proposing a vision in which the building stock plays a key role. The classical approach to transition, assessed by technical parameters, is challenged to reflect on new life cycles that propose attitudes with systemic potential and a long-term perspective.To face the contradictions between consumption and abandonment, is now necessary to develop approaches driven by broad objectives that translate global intentions into local impacts. Looking at the deep re-interpretation proposed by recycling projects (4), new possibilities can be found in tackling buildings as possible drivers for a city’s creation (5) based on available resources. Projects such as the Zinneke in Brussels, Luise 19E by Undjurekbrüggen, and Peveril Garden and Studio by Sanchez Benton architects outline three ways of dealing with the contemporary need for urgency and durability according to different targeted effects on context.Through the analysis of the case studies, however rare in the panorama, we will extract replicable principles and actions capable of having a direct impact on the environmental context and also a didactic potential based on the possible repeatability of the approach and contextual declination. The aim is to identify research perspectives based on realism and pragmatism that can be translated into widespread practices, connecting environmental culture and communities.1. Bennett, John W. The Ecological Transition: Cultural Anthropology and Human Adaptation. AldineTransaction, 1976.2. Harris, S., “Everyday architecture.” In Architecture of the Everyday, edited by S. Harris, D. Berke, Princeton Architectural Press, 1997.3. Ciorra, P. and Marini, S. (edited by), Re-cycle Italy. Strategie per l’architet- tura, la città e il pianeta. Electa, 2011.4. Bocchi R., “Recycle”. In Recycle theory. Dizionario illustrato / Illustrated dictionary, edited by S. Marini and G. Corbellini Quodlibet, 2016.5. De Carlo G., “È tempo di girare il cannocchiale.” Spazio e società, no. 54, (1991): 4-5.